Re-Mar: Repository of Marine Learning Objects - Behr, André; Cascalho, José; Guerra, Hélia; Costa, Ana; Parente, Manuela; Botelho, Andrea; Vicari, Rosa; Mendes, Armando (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2021: Anais do XII Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos NaturaisDO - 10.5753/wcama.2021.15745, 2021)
Current literature shows the lack of learning object repositories exclusively related to environmental education and that there is no predominant software. This paper presents Re-Mar, a marine learning object repository based on open source software. Re-Mar is a part of an effort to promote ocean literacy through educational content for students and teachers. The repository is supported by computational technologies to catalog and organize learning objects to retrieve and reuse. Our prototype shows that is possible to store, catalog, retrieve, and link learning objects to support environmental education and coping with learning objects lifecycle. This is the first step to future aggregation of linked data, ontologies, and artificial intelligence aspects.